Molecular Variation and Evolutionarily Significant Units in the Endangered Gila Topminnow - Karen M. Parker; Ruby J. Sheffer; Philip W. Hedrick (Conservation Biology, 1999)
Determining evolutionarily significant units in endangered species is one of the most significant challenges facing conservation biology. Often genetic information has been used as the primary basis of recommendations for evolutionarily significant units, but these data should be evaluated carefully and used in conjunction with other information. The endangered Gila topminnow ( Poeciliopsis. o. occidentalis ) has been the subject of extensive conservation biology research and genetic investigation. We extended these data to highly variable genetic markers, examined variation in microsatellite loci, and compared it with previous measures of genetic diversity for the Gila topminnow from the four watersheds in Arizona in which they are still naturally extant. Fish from Monkey Spring were the most highly differentiated from the other populations. Overall, the amounts and patterns of genetic variation were consistent with known historical and physical differences among sites. The four watersheds are highly physically isolated from one another and differ in a number of important factors in their physical habitat, biota, and the life‐history of the topminnows. Based on these geographic patterns and the genetic results, we recommend that the four watersheds all be managed and conserved separately.

Fitness in the Endangered Gila Topminnow - Ruby J. Sheffer; Philip W. Hedrick; W. L. Minckley; Anthony L. Velasco (Conservation Biology, 1997)
The Gila topminnow (Poeciliopsis o. occidentalis) is a small, live‐bearing, endangered fish extant in a maximum of nine locales in four separate watersheds in the United States. To determine if these populations differed in their fitness, we obtained samples from the four watersheds and examined them for four fitness correlates: survival, growth rate, fecundity, and bilateral asymmetry. Earlier research found that one population, Sharp Spring, had higher allozyme heterozygosity than the other three and had higher survival, growth rate, and fecundity and lower bilateral asymmetry than a sample from one of the other populations with no polymorphic allozyme loci, Monkey Spring. We also verified that Sharp Spring fish were polymorphic for the same allozyme loci whereas the Monkey Spring population was not. We did not, however, find positive associations of allozyme heterozygosity with the four fitness correlates for the four samples. Because the earlier study had much lower survival, it is likely that the differences resulted from differential response of the two populations to a stressful laboratory environment. Whether this unknown stress occurs in natural environments or its effect is predictive of other stresses remains unresolved. As a result, we concur with suggestions in the draft recovery plan that topminnows from nearby sources be used for reintroductions and that the Sharp Spring stock not be used outside the upper Santa Cruz River drainage.